WTO negotiations and accession issues for vulnerable economies - Rolf J. Langhammer; Matthias Lücke (Kiel Institute of World Economics (IfW), 2000)
The paper discusses the costs and benefits to be expected by least-developed and low-income (`vulnerable') economies if they accede to the WTO, the impact of current debates about WTO reform on vulnerable economies, and measures to make it easier for vulnerable economies to accede to and actively participate in the WTO. The main conclusion is that the benefits from WTO membership in terms of improved market access for traditional exports are likely to be limited. However, by submitting a wide range of trade-related policies to international scrutiny and by entering into binding commitments on the conduct of these policies, reform-oriented governments in vulnerable economies can make it more likely that their reforms will be successful.
Keywords: F13; 330; WTO-Regeln; Mitgliedschaft; Kosten-Nutzen-Analyse; Außenhandelsliberalisierung; Technische Hilfe; Verhandlungen; Entwicklungsländer; Welt